An insight on the (Hindu’s) unified quantum cosmology - UV., Satya Seshavatharam; S., Lakshminarayana (International Journal of Advanced Astronomy, 2015)
In the heuristic approach, with reference to ‘conservation of energy’, ‘initial light speed expansion’, ‘continuous light speed rotation’, ‘Kerr-Schwarzschild radius’, ‘conservation of centripetal force’, ‘Planck scale’, ‘quantum gravity’ and ‘Hindu model of cosmic age’, we introduce a heuristic ‘model of cosmology’. The authors would like to stress the fact that, ‘with light speed rotation’ qualitatively ‘Hubble parameter’ and ‘angular velocity’ both can be shown to be secondary physical constants and their individual roles can be shown to be similar. With five unified, simplified and workable assumptions, a number of useful cosmological formulae can be generated. With reference to current microwave back ground temperature obtained magnitude of current Hubble parameter is accurately fitting with the recommended value. With the proposed assumptions:1) the intended purpose of ‘lambda’ term can be understood and in future it can be relinquished. 2) Cosmic acceleration and dark energy concepts can be relinquished at fundamental level. 3) Cosmic flatness can be well understood.4) Comic ‘horizon problem’ can be eliminated at fundamental level. In future, either from ‘academic interest’ point of view or from ‘serious research’ point of view, this model can be recommended for in depth analysis at fundamental level.